THE DILEMMA OF HEALTH SECURITY AND ECONOMIC SECURITY IN HANDLING CORONAVIRUS DISEASE (COVID-19) CASE STUDY: MAKASSAR RECOVER POLICY - Miftah Farid Darussalam; Ayu Rezky Safaat; Maya Madya Agustin (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2022)
International security studies have developed and expanded from the scope and actors involved. The emergence of new threats, such as the spread of disease, requires the state to shift the referent object of security to focus on the individual. The Coronavirus Disease (COVID-19) phenomenon is a new thing that requires a quick response from the state and local governments. This response is needed to suppress the resulting impact so that it does not grow and spread to various fields. This study aims to assess the implementation of the Makassar Recover policy to handle COVID-19 through the Human Security Concept. It starts by comparing several state policies and more specifically looking at local government policies in Indonesia in dealing with the COVID-19 phenomenon. This study uses descriptive qualitative methods and interviews with several parties related to the COVID-19 phenomenon. The approach used is the concept of Human Security to measure the form of secured threats and objects. The study results that the implementation of the Makassar Recover policy has a dilemma in determining the priority of objects that should be secured. In the case of the COVID-19 phenomenon, it is still difficult for central and regional government policies to determine policy priorities that are directed at the economy or health sector. In this study, the results are that the Makassar Recover Policy should be implemented in stages. The health security sectors should be the priority, not economic security. Because the COVID-19 phenomenon has an existential threat to health security, economic security is still at the stage of vulnerability